Evolutionary adaptation is facilitated by the presence of lethal genotypes - Viktoria Blavatska; Bartlomiej Waclaw (Physical Review Research, 2024)
The rate of adaptation in theoretical models of biological evolution generally increases with the mutation rate. However, there is a threshold beyond which mutations into lethal states lead to extinction. It would be logical to assume that eliminating such lethal states could be advantageous for evolution. Here, we demonstrate that lethal mutations actually accelerate adaptation on rugged fitness landscapes with multiple peaks and valleys in the presence of competition for resources. We investigate a modified stochastic version of the quasispecies model, incorporating two types of genotypes—viable and lethal—and show that higher rates of lethal mutations result in shorter evolution times towards the best-fit genotype. This phenomenon can be attributed to an increased frequency of traversing fitness valleys, facilitated by reduced selection pressure against less-fit variants.